2022
DOI: 10.1371/journal.pone.0276512
|View full text |Cite
|
Sign up to set email alerts
|

We know but we hope: A qualitative study of the opinions and experiences on the inclusion of management, health economics and research in the medical curriculum

Abstract: The achievement of global and national health goals requires a health workforce that is sufficient and trained. Despite considerable steps in medical education, the teaching of management, health economics and research skills for medical doctors are often neglected in medical curricula. This study explored the opinions and experiences of medical doctors and academic educationalists on the inclusion of management, health economics and research in the medical curriculum. A qualitative study was undertaken at fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Table 1 outlines the attributes and levels for the final DCE that were developed from literature reviews, qualitative research, 4 think-aloud interviews with medical doctors and a quantitative pilot DCE (n=41).…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 outlines the attributes and levels for the final DCE that were developed from literature reviews, qualitative research, 4 think-aloud interviews with medical doctors and a quantitative pilot DCE (n=41).…”
Section: Methods and Analysismentioning
confidence: 99%
“…The medical curriculum is all too often informed by historical content where clinical training surpasses any other topic or competency 1–3. A recent qualitative research study of medical doctors and academic educationalists from four medical schools in Southern Africa found that the teaching of management, and to a lesser extent research, was ad hoc and unstructured 4. There was consensus among participants that both need to be incorporated formally but that this would incur opportunity costs in terms of time taken away from clinical training.…”
Section: Introductionmentioning
confidence: 99%
“…The leadership and managerial expectations of doctors are immediate and evolving, even in the absence of formal training. [5,6] '...as an intern I was managing just the ward, as well as the nursing staff there. But now as a resident, I'm now at a point where even at national level, I attend meetings with different stakeholders, where I'm supposed to collaborate with them, work with them, as well as advocate for the community, as well as sort of be the leader with some of the junior people within those meetings…so you should be able to present those leadership skills.... ' [D 2] In the absence of training, doctors have to either 'learn on the job' [D 4] or pursue additional training, often at their own expense.…”
Section: Sub-theme 12: High Levels Of Leadership and Managerial Respo...mentioning
confidence: 99%
“…[4,5] In 2021, the perceptions of graduates and medical educators (ME) on the roles of leadership and management, and other non-traditional topics in the curriculum, were explored in a doctoral study conducted at four medical schools in southern Africa, including the UB FOM. [6] This short report describes the perceptions of graduates and MEs on leadership and management training at UB, the most recently established participating university which continues to revise its curriculum. Table 1 outlines the current inclusion of leadership and management in the curriculum.…”
mentioning
confidence: 99%